2000
DOI: 10.1302/0301-620x.82b1.0820055
|View full text |Cite
|
Sign up to set email alerts
|

Experience in the treatment of dedifferentiated chondrosarcoma

Abstract: Dedifferentiated chondrosarcoma is a rare, highly malignant variant of chondrosarcoma in which a high-grade spindle-cell sarcoma coexists with a lower-grade chondroid tumour. We have reviewed our experience with this neoplasm in 22 patients, all of whom were treated using modern oncological principles of planned resection and chemotherapy. Despite this the median survival was under nine months and only 18% were alive at five years. Those patients who received chemotherapy, and in whom wide margins of excision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
96
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(103 citation statements)
references
References 4 publications
5
96
2
Order By: Relevance
“…Several preclinical efforts are currently underway to develop targeted therapy for dedifferentiated chondrosarcoma based on molecular approaches [14,15,17]. The low survival rates of patients we observed with dedifferentiated chondrosarcoma are comparable to those reported in previous studies (Table 3) [3,5,9,10,13,18,21,22]. This indicates the need for more systemic options.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Several preclinical efforts are currently underway to develop targeted therapy for dedifferentiated chondrosarcoma based on molecular approaches [14,15,17]. The low survival rates of patients we observed with dedifferentiated chondrosarcoma are comparable to those reported in previous studies (Table 3) [3,5,9,10,13,18,21,22]. This indicates the need for more systemic options.…”
Section: Discussionsupporting
confidence: 83%
“…Studies performed to date have not identified efficacious chemotherapy agents [3,5,9,10,13,18,21,22]. We therefore sought to determine diseasespecific survivorship (as well as local recurrences and metastases), prognostic variables associated with patient survival, and toxicities associated with ifosfamide-based chemotherapy for patients diagnosed with dedifferentiated chondrosarcoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study seemed to show an effect on survival [77], which was not confirmed by others [37,78,79]. For peripheral dedifferentiated chondrosarcoma, arising in osteochondroma, chemotherapy led to longer survival in a small retrospective report [80].…”
Section: Systemic Treatmentmentioning
confidence: 91%
“…Because the diagnoses were variable, expected survival would be guided by histopathologic diagnoses and stage at presentation. Despite the particularly poor prognosis associated with dedifferentiated chondrosarcomas [4,9,13,23], two of the three patients with this diagnosis were alive without disease. Although a somewhat surprising finding, long-term followup would be necessary to make additional comment on survival impact in this series.…”
Section: Discussionmentioning
confidence: 97%